Meningkatkan Membaca Permulaan Melalui Media Interaktif Pada Anak Dengan Gangguan Spektrum Autisme Di Kelas II Di SLB Negeri Autis Sumatera Utara - Nadiana Nasution; Johandri Taufan; Zulmiyetri Zulmiyetri; Rilla Muspita (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to improve early reading skills and to describe the learning process through the use of interactive media for children with Autism Spectrum Disorder (ASD). The research employed a Classroom Action Research (CAR) method conducted at a Public Special School for Autism in North Sumatra. The research subjects consisted of three second-grade students with Autism Spectrum Disorder, identified as MS, FA, and MR. Based on the initial assessment, the students’ early reading abilities were categorized as low, characterized by difficulties in letter recognition, syllable blending, and maintaining learning focus. The study was carried out in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The results indicated a gradual improvement in the learning process through the use of interactive media. In Cycle I, students began to show increased attention, learning interest, and basic reading abilities, although intensive teacher guidance was still required. Quantitatively, early reading achievement in Cycle I reached 60% for MS, 57.5% for FA, and 58.5% for MR. In Cycle II, the learning process became more optimal, as reflected in higher active participation, greater independence, and improved reading fluency. Learning outcomes also showed a significant increase, with achievement scores of 71.2% for MS, 71% for FA, and 71.5% for MR. These findings indicate that interactive media are effective in improving both the learning process and early reading outcomes of second-grade students with Autism Spectrum Disorder at the Public Autism Special School in North Sumatra.